Comparative analysis of environmental education legislation in the Conceição do Araguaia microregion, Pará state (Research, Society and Development, 2022)
The realization of a solid Environmental Education in municipalities goes through the formulation of modern legislation. Thus, this research aimed to analyze the municipal legislation that deals with EE in the city of Conceição do Araguaia-PA, comparing the legislation of the towns of Floresta do Araguaia, Santa Maria das Barreiras and Santana do Araguaia. The study was developed in the Microregion Conceição do Araguaia. It has a qualitative approach. After all, it seeks to analyze and interpret deeper aspects of the researched theme and a quantitative one because it carries out the comparative analysis of municipal environmental education legislation. We used procedures derived from bibliographic research and documentary research. The research was carried out on the following sites of the municipal councils and home pages of the city halls of the municipalities surveyed, with the following descriptors: environmental education, environmental, environment, and environment. The legislation was initially classified and verified the presence of the theme EE. At the end of the initial analysis, comparisons of environmental education legislation between municipalities were made and presented in a comparative table. The results show that the city of Conceição do Araguaia has the largest legislative framework, followed by Santa Maria das Barreiras. The cities of Floresta do Araguaia and Santana do Araguaia have a legislative deficit with EE themes. In view of the results presented in this research, verifies the need for the creation of municipal legislation that focuses on strengthening environmental education to achieve sustainability.